Penanaman Biofarmaka Berbasis Agroforestry di Desa Sukaresmi, Kecamatan Rancabali, Kabupaten Kuningan - Bella Oktavianita; Kiki wasilatus sofyana (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Cultivating medicinal plants for farmers is felt not to be economically beneficial because for them the market is still unclear. Different from planting rice, corn, soybeans which have good market and market value. In addition, the availability of raw materials for medicinal plants is difficult because there are few farmers who cultivate them. Medicinal plants or known as biopharmaca are plants that have medicinal properties or uses, especially for families in Sukaresmi Village, Rancabali District, Kuningan Regency. The purpose of community service activities carried out is to help improve community knowledge and skills about the importance of using biopharmaca plants as medicines that are useful for health. The activity was carried out in Sukaresmi Village with the main target being the village community. Implementation of activities starts from the stages of preparation, implementation, and evaluation of activities. The results of the activities after community service show that the community's knowledge and skills regarding the use of biopharmaca plants as superior products have improved compared to the pre-activity condition. Key words: Agroforestry-based, Biofarmaka Planting, Sukaresmi Village